Antagonism of rhizosphere Trichoderma brevicompactum DTN19 against the pathogenic fungi causing corm rot in saffron (Crocus sativus L.) in vitro - Tian, Li; Zhu, Xinyu; Guo, Yingqiu; Zhou, Qianjun; Wang, Lili; Li, Wankui (Frontiers in Microbiology, 2024)
Corm rot in saffron (Crocus sativus L.) significantly impacts yield and quality. Non-toxic fungi, particularly Trichoderma species, are valuable for biological control due to their production of diverse and biologically active secondary metabolites. This study aimed to isolate an effective antagonistic fungus against the pathogenic fungi causing corm rot in saffron. Four pathogenic fungi (Fusarium oxysporum, Fusarium solani, Penicillium citreosulfuratum, and Penicillium citrinum) were isolated from diseased saffron bulbs in Chongming. Initial screening through dual culture with these pathogens identified Trichoderma brevicompactum DTN19 from rhizosphere soil samples of C. sativus based on its inhibitory effects through volatile, nonvolatile, and fermentation broth metabolites. F. oxysporum was identified as the most severe pathogen. SEM (scanning electron microscope) and TEM (transmission electron microscope) observations revealed that T. brevicompactum DTN19 significantly inhibited the growth and development of F. oxysporum mycelium, disrupting its physiological structure and spore formation. Additionally, T. brevicompactum DTN19 demonstrated nitrogen fixation and production of cellulase, IAA (Indole acetic acid), and siderophores. Whole-genome sequencing of strain DTN19 revealed genes encoding protease, cellulase, chitinase, β-glucosidase, siderophore, nitrogen cycle, and sulfate transporterrelated proteins. Overall, T. brevicompactum DTN19 showed the development prospect of biological agents.